Regenerative endodontic procedures for avulsed immature permanent tooth with severe external root resorption - สิทธิสร วิศรุต; จิรเดโชชัย ภาณุพงษ์ (Thai Endodontic Journal, 2025)
Infection-related root resorption following the reimplantation of an avulsed tooth is a common and severe adverse outcome. This condition is particularly aggressive in teeth with immature root development. Additionally, treatment procedures are highly challenging due to difficulties in root canal disinfection, halting root resorption, and managing the immature root structure. The objective of this case study is to demonstrate the application of regenerative endodontic procedures in the treatment of an avulsed immature permanent tooth with severe infection-related root resorption. The treatment protocol included thorough root canal irrigation and the use of intracanal medication with triple antibiotic paste to eliminate infection and prevent further root resorption. After a 5-month disinfection period, during which the periapical lesion decreased in size, a blood clot was induced in the root canal, followed by coronal sealing. At the 1-year follow-up, the patient remained asymptomatic. Radiographic evaluation revealed cessation of root resorption, complete resolution of the periapical lesion, and restoration of continuous alveolar bone around the root surface. These case reports suggest that regenerative endodontic procedures can offer a promising treatment outcome for avulsed immature permanent teeth affected by infection-related root resorption.